Performance Evaluation of Improved Lasora (Cordia myxa L.) Varieties for Growth and Yield under Limited Irrigation in India’s Hot Arid Region: RESEARCH PAPER - Meghwal, Purkha Ram; Dheeraj Singh; Sourabh (Annals of Arid Zone, 2025)
Lasora (Cordia myxa L.) is an underutilized fruit-cum-vegetable crop that has gained commercial importance in arid regions due to its adaptability under limited irrigation and diverse soil and climatic conditions. This study was aimed to evaluate the vegetative growth, fruit yield, and physical parameters of three improved lasora varieties—Maru Samridhi, Karan Lasoda, and Thar Bold under limited irrigation in the hot arid region of India. The experiment was conducted at ICAR-Central Arid Zone Research Institute, Jodhpur, using budded plants of the three varieties in a randomized complete block design with seven replications. Data were recorded from the third year onwards and analyzed statistically. Results showed that Maru Samridhi exhibited superior vegetative growth, with the tallest plants (pooled height: 2.84 m) and the highest fruit yield (9.74 kg plant-1). Karan Lasoda demonstrated the largest canopy area (8.78 m²) and the longest fruits (24.34 mm), while Thar Bold showed balanced performance across most parameters. Maru Samridhi also had the highest pulp-to-stone ratio (9.26), indicating better fruit quality. These findings highlight the potential of Maru Samridhi for high productivity and Karan Lasoda for maximizing ground coverage and fruit size in arid regions. The study provides valuable insights for selecting suitable lasora varieties based on specific cultivation goals and environmental conditions.